2022
DOI: 10.3389/fbioe.2022.1071472
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament stem cell-based bioactive constructs for bone tissue engineering

Abstract: Objectives: Stem cell-based tissue engineering approaches are promising for bone repair and regeneration. Periodontal ligament stem cells (PDLSCs) are a promising cell source for tissue engineering, especially for maxillofacial bone and periodontal regeneration. Many studies have shown potent results via PDLSCs in bone regeneration. In this review, we describe recent cutting-edge researches on PDLSC-based bone regeneration and periodontal tissue regeneration.Data and sources: An extensive search of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…Periodontal ligament (PDL) cells have emerged as invaluable cell sources for probing ligament regenerative mechanisms and cell biology [ [22] , [23] , [24] , [25] ]. Occupying a unique mechanical niche subjected to forces during mastication and swallowing, PDL cells likely harbor specialized tensional responsiveness [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal ligament (PDL) cells have emerged as invaluable cell sources for probing ligament regenerative mechanisms and cell biology [ [22] , [23] , [24] , [25] ]. Occupying a unique mechanical niche subjected to forces during mastication and swallowing, PDL cells likely harbor specialized tensional responsiveness [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant advances have been made in the field of hPDLSC-based therapy. From their discovery, various attempts to induce periodontal regeneration have been made by combining hPDLSCs with scaffolds or membranes and with signaling molecules [26,27]. Cell-sheet technologies have also been developed via approaches that can involve or not the use of scaffolds aimed at supporting cell attachment, proliferation and 3D tissue organization [28,29].…”
Section: Hpdlscs As Therapeutic Tool: Current Statusmentioning
confidence: 99%
“…Osteogenic differentiation of PDLSCs is an important event in the repair of alveolar bone defects in periodontitis [ 7 ]. A large number of studies have shown that PDLSCs can be used to treat periodontal bone defects [ 8 ]. However, their source and osteogenesis ability are limited, and the safety of stem cell therapy largely restricts their clinical application [ 9 ].…”
Section: Introductionmentioning
confidence: 99%